Palatal Abscess of Odontogenic Origin Causing Dyspnea in an Elderly Patient: A Case Report and Critical Review of Management Strategies - I Dewa Gede Arta Eka Putra; Putu Dian Ariyanti Putri; Ketut Tadeus Max Nurcahya Pinatih; Made Gede Krisna Rendra Kawisana (Archives of The Medicine and Case Reports, 2026)
Odontogenic infections are prevalent clinical entities, typically presenting as localized pathologies within the alveolar process. However, a palatal abscess—a specific manifestation arising from the spread of infection through the palatal cortical plate of maxillary teeth—rarely escalates to cause life-threatening airway compromise. This report details an exceptional case of a palatal abscess causing significant dyspnea in an elderly patient, challenging the conventional understanding of the hard palate as a robust anatomical barrier preventing deep space extension. A 68-year-old female presented to the emergency department on October 1st, 2022, with a five-day history of progressively enlarging palatal swelling, dysphagia, and dyspnea. Clinical examination revealed a massive, fluctuant mass extending from the hard to the soft palate, obstructing the oropharyngeal inlet. Despite a leukocyte count at the upper limit of normal and an afebrile status—indicative of geriatric immunosenescence—the patient exhibited objective tachypnea (24 breaths/min). Diagnosis was confirmed via needle aspiration. Management involved immediate airway stabilization, broad-spectrum antibiotics (Ceftriaxone and Metronidazole), and corticosteroids. On October 3rd, 2022, the patient underwent incision and drainage under general anesthesia, yielding 15cc of purulent material. The source was identified as carious residual roots of the maxillary right second molar (FDI #17). Post-operative recovery was rapid, with discharge on October 6th, 2022. In conclusion, this case underscores that palatal abscesses can evolve into critical airway emergencies, particularly in geriatric patients with diminished physiological reserves and blunted immune responses. Prompt recognition, aggressive multidisciplinary management, and definitive dental treatment are paramount to preventing mortality.